2014
DOI: 10.3390/rs6098541
|View full text |Cite
|
Sign up to set email alerts
|

How Reliable is the MODIS Land Cover Product for Crop Mapping Sub-Saharan Agricultural Landscapes?

Abstract: Abstract:Accurate cropland maps at the global and local scales are crucial for scientists, government and nongovernment agencies, farmers and other stakeholders, particularly in food-insecure regions, such as Sub-Saharan Africa. In this study, we aim to qualify the crop classes of the MODIS Land Cover Product (LCP) in Sub-Saharan Africa using FAO (Food and Agricultural Organisation) and AGRHYMET (AGRiculture, Hydrology and METeorology) statistical data of agriculture and a sample of 55 very-high-resolution ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 46 publications
4
35
0
1
Order By: Relevance
“…However, for the purposes of comparison, a constant value of 0.5 (i.e., 50%) was used. This is in line with the assumptions made by previous studies (e.g., [3,10]). …”
Section: Accuracy Assessmentsupporting
confidence: 79%
See 4 more Smart Citations
“…However, for the purposes of comparison, a constant value of 0.5 (i.e., 50%) was used. This is in line with the assumptions made by previous studies (e.g., [3,10]). …”
Section: Accuracy Assessmentsupporting
confidence: 79%
“…Compared to their estimates, errors in the MODIS_FCM can be considered to be consistent due to the aforementioned relatively small variation in MAE, although the number of validation sites used could have influenced the degree of variation. In terms of overall accuracy, the value obtained in this study represents a significant improvement over the reported 51% for the MODIS_LCP [3], which has been found to have a better accuracy than most global LULC products [10].…”
Section: Accuracy Assessment At the Regional Scalementioning
confidence: 56%
See 3 more Smart Citations